Plant MLO proteins: Conserved "disease susceptibility factors" for powdery mildew fungi - Panstruga, Ralph (My University, 2015)
Powdery mildew is a widespread plant disease of temperate climates that is caused by ascomycete fungi of the order Erysiphales. The disease is macroscopically characterized by “powdery” fungal reproduction structures on the surface of plant organs. It is an important threat for both agri- and horticulture and can cause significant harvest losses in cereals and crop plants such as wheat, barley, and tomato, and severely impact ornamental plants such as roses. Accordingly, the generation of plant breeds that exhibit robust immunity to this disease is of great economic interest. One major step in this direction was the discovery of barley mutant plants that display near complete resistance to the barley powdery mildew pathogen, Blumeria graminis f.sp. hordei (Bgh). These plants, which carry recessively inherited loss-of-function mutations in the gene Mildew resistance locus o (Mlo), show durable broad-spectrum resistance against virtually all Bgh isolates. On mlo mutant plants, powdery mildew pathogenesis is terminated at the stage of cell wall penetration and host cell entry; consequently, fungal sporelings do not form haustoria inside host cells and fungal colonies cannot develop. Subsequent studies revealed that (1) Mlo genes are restricted to plants and green algae and represented as small to medium-sized families in higher plant species and (2) that mlo-based powdery mildew resistance is not restricted to the monocot barley, but also found in the distantly related eudicot plant species Arabidopsis thaliana. Mutant alleles of Arabidopsis thaliana AtMLO2, one out of the 15 MLO genes present in the Arabidopsis genome, confers partial resistance to the adapted powdery mildew species Golovinomyces orontii and G. cichoracearum.
Keywords: Mildiu; MLO proteins; Powdery mildews; Effectors